1995
DOI: 10.1007/bf00178354
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of massive bone allografts in limb-preserving operations for bone tumours

Abstract: This study analysed the influence of several factors affecting the consolidation time of 83 massive bone allografts in 79 patients with malignant bone tumours: osteosarcoma 57; Ewing's sarcoma 8; malignant fibrous histiocytoma 3; chondrosarcoma 4; fibrosarcoma 5; and giant cell tumours 2. The mean age of the patients was 19 years and the mean length of the allografts was 18 cm. The minimum follow up was for 12 months. The mean consolidation time for metaphyseal and diaphyseal osteotomies was 6.5 and 16 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…A review of literature reveals lower nonunion rates for combined allograft and vascularised fibula reconstructions (up to 31%) in comparison to allograft alone (nonunion in up to 46%) (Tables 1 and 2) [11, 12, 14, 20, 22, 23, 27, 3038, 54]. Among our twelve patients, four developed nonunion.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A review of literature reveals lower nonunion rates for combined allograft and vascularised fibula reconstructions (up to 31%) in comparison to allograft alone (nonunion in up to 46%) (Tables 1 and 2) [11, 12, 14, 20, 22, 23, 27, 3038, 54]. Among our twelve patients, four developed nonunion.…”
Section: Discussionmentioning
confidence: 82%
“…Ten-year graft survival rates of approximately 80% had been reported (range 53% to 84%) [8, 14–16, 18]. Long-term results of several study groups report a steady state without deterioration of the graft if the allograft endures the first three years, suggesting that it will thereafter remain functional for the duration of patient's life [9, 11, 12, 16, 18, 22, 4951, 53, 54]. Good functional long-term results are achieved with intercalary allografts, but associated complications as nonunion, fracture, and infection are frequent (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The consolidation time for allografts has been reported as being 9 to 15 months. 19,28 Aranguren et al 31 have also observed faster consolidation in the metaphysis than in the diaphysis in allografting (6.5 vs 16 months). Ceruso et al 32 reported a similar mean consolidation time of eight months with allografts combined with a vascularised fibular graft.…”
Section: Discussionmentioning
confidence: 92%
“…Deijkers et al ( 40 ) revealed that the mean consolidation time was 17 months in diaphyseal junctions, and 13.4 months in metaphyseal junctions. San Julian Aranguren et al ( 46 ), identified that the mean consolidation time for the diaphyseal allograft reconstruction was 16 months, and systemic chemotherapy or external radiotherapy delayed consolidation. Brunet et al ( 47 ) reported that the cumulative probability of union was only 46% (95% CI, 0–99%) at 1 year.…”
Section: Discussionmentioning
confidence: 99%